(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to demonstrate the extent of the relationship of influence and correlation between negotiation skills in its dimensions (planning and preparation skill, persuasion and influence skill, communication skill, and objection skill) as an independent variable in organizational conflict in its dimensions (difference in values, difference in goals and interests, dependency between parliamentary committees, and organizational change) as a dependent variable of a sample of parliamentary committee chairs in the Iraqi Council of Representatives. The problem of the study lies mainly in the high intensity of organizational conflict within the organization under study.The descriptive analytical approach was also adopted during it. The questionnaire was considered the main tool for collecting data. A number of statistical methods were used in addition to appropriate statistical analytical programs in the process of analyzing and processing data. The research sample was selected from the heads of parliamentary committees, which numbered (25) committees, represented by (the head of the committee, the deputy head of the committee, and the second deputy head of the committee), thus the size of the sample under study reached (75) members to whom the questionnaire was distributed, and (70) valid questionnaires were retrieved for analysis. This study resulted in a number of conclusions, the most important of which is (the existence of a correlation and influence relationship between the study variables). The study recommended the necessity of adopting advance planning to confront the difficulty of reaching an agreement during negotiations, taking into consideration the necessity of selecting members of the negotiating team from members who possess the abilities to negotiate and persuade.